APPLICATION OF THE PRINCIPLES OF JUSTICE TO PKPU APPLICATIONS BY DEBTORS AND BANKRUPTCY APPLICATIONS BY CREDITORS - Apriyanto, Hendra; Raspita, Desni (JILPR Journal Indonesia Law and Policy Review, 2024)
Bankruptcy law is seen as a solution to the problem of debts and receivables that burden debtors who no longer have the ability to pay their debts to their creditors. PKPU is a period provided by law through a commercial judge's decision, during which the parties, namely creditors and debtors, are given the opportunity to discuss and agree on how to make debt payments by providing a payment plan for all or part of the debt. Request for Postponement of Debt Payment Obligations (PKPU) is a mechanism in bankruptcy law that provides an opportunity for debtors who are experiencing debt payment difficulties to carry out debt restructuring. Based on Law Number 37 of 2004 concerning Bankruptcy and PKPU, both debtors and creditors can apply for PKPU. The type of research used in this research is normative juridical. The application of the provisions regarding PKPU has given rise to various debates related to the principle of justice, namely that the application of the concept of justice in resolving bankruptcy cases can be interpreted as a situation where the debtor stops paying his debts which are due in social life in society. The principle of justice in resolving bankruptcy cases is defined as a commercial solution to get out of debt and receivable problems that are pressing on a debtor, so that the bankruptcy institution functions as an alternative institution for resolving debtor obligations towards creditors more effectively and efficiently.